Cancer in the Arab World - Al-Shamsi, Humaid O.; Abu-Gheida, Ibrahim H.; Iqbal, Faryal; Al-Awadhi, Aydah; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This is an Open Access book. This book is a must-have for healthcare providers and researchers, public health specialists and policy makers who are interested and involved in cancer care in the Arab world. The Arab world consists of 22 countries, which are members of the Arab League and spanning over 13,132,327 km2 with over 423,000,000 population. Over the past few decades, the Arab world has witnessed a swift evolution in healthcare provision. Nonetheless, Arab countries have considerable variability in economic capabilities, resource allocation, and intellectual talent that inevitably reflect on access to modern cancer care and prevention. This book is authored by experts from the Arab world who provide vital information on cancer statistics and risk factors, available clinical care pathways and infrastructure, and prevention programs in their individual countries. The chapters also address specific challenges in each country andinsights into future directions to achieve optimal care with conventional and novel diagnostics and therapies to keep up with the era of precision medicine. Special topics of interest and unique to the Arab world are also discussed, such as out of the country$1 (Bs medical tourism for cancer care and cancer care during war and conflict. Other special chapters include: Cancer research in the Arab world, Radiation therapy in Arab World and Pediatric Oncology in the Arab World Cancer in the Arab World is the first comprehensive book that addresses cancer care in depth in all Arab countries and it is endorsed by the prestigious Emirates Oncology Society.s
1 Introduction -- 2 General Oncology Care in Algeria -- 3 General Oncology Care in Bahrain -- 4 General Oncology Care in Egypt -- 5 General Oncology Care in Iraq -- 6 General Oncology Care in Jordan -- 7 General Oncology Care in Kuwait -- 8 General Oncology Care in Lebanon -- 9 General Oncology Care in Libya -- 10 General Oncology Care in Mauritania -- 11 General Oncology Care in Morocco -- 12 General Oncology Care in Oman -- 13 General Oncology Care in Palestine -- 14 General Oncology Care in the Kingdom of Saudi Arabia -- 15 General Oncology Care in Somalia -- 16 General Oncology Care in Sudan -- 17 General Oncology Care in Syria -- 18 General Oncology Care in Tunisia -- 19 General oncology care in the UAE -- 20 General Oncology Care in the Republic of Yemen -- 21 General Oncology Care in Qatar, Comoros & Djibouti -- 22 Breast Cancer in the Arab World -- 23 Colorectal Cancer in the Arab World -- 24 Palliative Care in the Arab World -- 25 Cancer Research in the Arab World -- 26 Pediatric Oncology in the ArabWorld -- 27 Challenges Associated with Medical Travel for Cancer Patients in the Arab World: A Systematic Review -- 28 Radiation Therapy in Arab World -- 29 Cancer Care During War and Conflict.
Keywords: Oncology; Medical radiology; Medicine; Oncology; Radiation Oncology; Clinical Medicine